Rural Areas Between Regional Needs and Global Challenges Transformation in Rural Space - Leimgruber, Walter; Chang, Chang-yi David (Perspectives on Geographical Marginality, 2019)
This book provides an up-to-date account of the many processes shaping and transforming rural space in various parts of the world. The various case studies focus on the multi-functionality of the rural world and the driving forces behind it. The book demonstrates that rural areas are no longer simply characterized by an agricultural economy, and instead accommodate multiple complementary activities. It also touches upon two major changes that have taken place. The first is the process of rurbanization, which has led to the clear distinction between town and countryside becoming blurred: urban traits have penetrated rural areas, and rural traits have invaded towns. The second change is that rural areas are increasingly seen as multi-functional, providers not only of food and other natural resources but also locations for the generation of renewable energy (wind farms, solar farms, biogas) and regions for the preservation of biodiversity. These transformations have resulted in a new understanding and self-image of rural areas and their populations.